Aqueous liquid membrane process for recovery of BTX aromatics - I Dewa Gede Arsa Putrawan (Jurnal Teknik Kimia Indonesia, 2012)
An aqueous liquid membrane process has been developed for extracting BTX aromatics in catalytic reformate. The process mainly involved a multistage liquid-membrane permeator and two distillation towers. Continuous stirred vessels were utilized as contactors for permeation. Aqueous solution of saponin and light oil were used as liquid membrane and receiving phase, respectively. The equations of material balance, permeation, and constrain have been solved to study the effects of operating variables on the product yield and BTX purity. BTX purity up to 95% and yield of 90% could be achieved. The larger the values of solvent-to-feed ratio, stirring rate, number of permeation stages, permeator reflux ratio, or permeator volume, the greater the energy requirement. The energy supplied to the process is mainly utilized to recover solvent. Solvent-to-feed ratio was found to be the most influential variable on energy demand. The purity of BTX aromatics increases as the permeator reflux ratio and solvent-to-feed ratio increase or the stirring rate, number of permeation stages, and permeator volume decrease. The opposite trends are observed for the yield of BTX aromatics. The raffinate obtained was found to be a good blendstock for clean motor gasoline. Keywords: Liquid membrane, BTX Aromatic, Stirred vesselAbstrakProses membran cair akuatik telah dikembangkan untuk ekstraksi aromatik BTX dari reformat katalitik. Proses tersebut melibatkan permeator multitahap dan dua kolom distilasi sebagai alat utama. Tangki berpengaduk kontinyu digunakan sebagai alat kontak permeasi. Larutan saponin dalam air digunakan sebagai membran cair dan minyak ringan digunakan sebagai fasa penerima. Persamaan-persamaan neraca massa, permeasi dan kendala proses telah diselesaikan untuk mengkaji pengaruh berbagai variabel operasi terhadap perolehan produk dan kemurnian BTX. Kemurnian BTX hingga 95% dan perolehan hingga 90% dapat dicapai. Jika rasio pelarut-terhadap-umpan, laju pengadukan, jumlah tahap permeasi, rasio refluks permeator, atau volume permeator ditingkatkan, maka kebutuhan energi menjadi semakin besar. Energi yang dipasok ke dalam proses didominasi oleh pemulihan pelarut. Rasio pelarut-terhadap-umpan diketahui sebagai variabel yang paling berpengaruh terhadap kebutuhan energi. Kemurnian aromatik BTX semakin meningkat jika laju pengadukan, jumlah tahap permeasi, rasio refluks permeator, atau volume permeator dikurangi. Hal sebaliknya ditemukan untuk nilai perolehan aromatik BTX. Rafinat yang diperoleh diketahui sebagai bahan yang baik untuk gasolin motor ramah lingkungan.Kata kunci: Membran cair, Aromatik BTX, Tangki berpengaduk